Price exuberance episodes in private real estate - Cincinelli, Peter; Tsolacos, Sotiris; Urga, Giovanni (Journal of Financial Stability, 2024)
In this paper, we investigate price exuberance episodes in the main UK commercial real estate sectors – retail, offices and industrials - over the period December 1986–April 2022. Using the Backward Supremum Augmented Dickey Fuller approach of Phillips et al. (2015a,b), we find that episodes of price explosiveness are asynchronous across sectors with only common phase being the period 2003–2007. We also conduct a multivariate probit analysis to identify factors that indicate the occurrence of price exuberance episodes and generate early signals for possible price bubble building. The predictors for price explosiveness differ by sector with more consistent signals obtained from the yield curve for retail and industrials, rent growth for offices and industrials, and inflation for retail and offices. A key implication of this study is that the study of price exuberance and bubbles in private real estate should be sector specific even within the same country.